The Regio- and Stereospecific Intermolecular Dehydrative Alkoxylation of Allylic Alcohols Catalyzed by a Gold(I) N-Heterocyclic Carbene Complex - Mukherjee, Paramita (2013)
A 1:1 mixture of (IPr)AuCl [IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidine] and AgClO(4) catalyzes the intermolecular dehydrative alkoxylation of primary and secondary allylic alcohols with aliphatic primary and secondary alcohols to form allylic ethers. These transformations are regio- and stereospecific with preferential addition of the alcohol nucleophile at the γ-position of the allylic alcohol syn to the departing hydroxyl group and with predominant formation of the E stereoisomer. The minor α-regioisomer is formed predominantly through a secondary reaction manifold involving regioselective γ-alkoxylation of the initially formed allylic ether rather than via the direct α-alkoxylation of the allylic alcohol.